2018
DOI: 10.1016/j.jtho.2017.11.118
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic Syndromes and Thymic Malignancies: An Examination of the International Thymic Malignancy Interest Group Retrospective Database

Abstract: Previously, there have been mixed data regarding the prognostic role of PN/AI syndromes for patients with TETs. Here, using the largest data set in the world for TETs, PN/AI syndromes were associated with favorable features (i.e., earlier stage and complete resection status) but were not an independent prognostic factor for patients with TETs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
71
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 45 publications
6
71
1
Order By: Relevance
“…In the study by Padda et al . 33.0% of patients with thymomas had MG, which was similar to the incidence observed in the ITMIG database . However, thymomas located in the superior mediastinum were more frequently associated with MG than those located in the inferior mediastinum.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In the study by Padda et al . 33.0% of patients with thymomas had MG, which was similar to the incidence observed in the ITMIG database . However, thymomas located in the superior mediastinum were more frequently associated with MG than those located in the inferior mediastinum.…”
Section: Discussionsupporting
confidence: 78%
“…In the study by Padda et al 33.0% of patients with thymomas had MG, which was similar to the incidence observed in the ITMIG database. 31 However, thymomas located in the superior mediastinum were more frequently associated with MG than those located in the inferior mediastinum. There is no consensus on the pathophysiological link between thymomas and MG. 32 However, previous studies have demonstrated a correlation between MG and anti-AChR antibodies.…”
Section: Discussionmentioning
confidence: 95%
“…Thymic epithelial tumors are comprised of two different tumor types including thymomas and thymic carcinomas [9,18]. While thymomas are rare, they remain the most common mediastinal mass in adults, comprising up to 25% of mediastinal masses [2].…”
Section: Discussionmentioning
confidence: 99%
“…While it is well-recognized that these diseases may occur in the absence of a thymoma, the presence of a thymoma has been associated with a worse prognosis, which in some part, appears to be dependent on thymoma WHO classification and Masaoka staging [1-3, 9, 10]. In a large retrospective analysis, Padda et al noted that among different WHO thymoma classes, class B2 is most commonly associated with autoimmune and paraneoplastic disorders, whereas class AB thymomas are least commonly associated [9]. Furthermore, they noted that the presence of an autoimmune or neoplastic syndrome was not an independent prognostic factor for recurrence-free and overall survival in thymic epithelial tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with thymic neoplasms might be clinically indolent or present with thoracic symptoms. A wide range of autoimmune parathymic syndromes associated with thymic neoplasms has been reported . Myasthenia gravis is the most common parathymic syndrome in thymic neoplasm patients, followed by pure red cell aplasia and adult‐onset hypogammaglobulinemia.…”
Section: Introductionmentioning
confidence: 99%